2005
DOI: 10.1590/s1807-59322005000300002
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Nutritional Status and Food Intake in Hemodialysis Patients

Abstract: BACKGROUND: Patients in end-stage renal disease often suffer from poor appetite, various comorbidities, and dietary restrictions. Despite regular hemodialysis, nutritional imbalances are frequently reported. Aiming to correlate nutritional status with food ingestion, a prospective study was done in an outpatient group. METHODS: Stable patients undergoing chronic hemodialysis for at least 3 months (n = 44) were investigated by dietary recall and standard anthropometric, biochemical, and bioimpedance determinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
53
1
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 25 publications
7
53
1
6
Order By: Relevance
“…15 Protein intake values below the recommended ones are in accordance with the findings of several other studies, 20,24,[26][27][28][29] suggesting a negative nitrogen balance, which jeopardizes the nutritional status of HD patients. Slomowitz et al 30 have reported that some patients cannot maintain protein balance and lack of uremic toxicity with an energy intake of 25 to 35 kcal/kg/day and protein intake of 1.1 g/kg/day, requiring a slightly greater protein intake of 1.2 g/kg/day.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…15 Protein intake values below the recommended ones are in accordance with the findings of several other studies, 20,24,[26][27][28][29] suggesting a negative nitrogen balance, which jeopardizes the nutritional status of HD patients. Slomowitz et al 30 have reported that some patients cannot maintain protein balance and lack of uremic toxicity with an energy intake of 25 to 35 kcal/kg/day and protein intake of 1.1 g/kg/day, requiring a slightly greater protein intake of 1.2 g/kg/day.…”
Section: Discussionsupporting
confidence: 88%
“…The major underlying disease of the patients studied was hypertensive nephrosclerosis, followed by diabetic nephropathy, which are complications of adults and elderly, in accordance with the 2008 census 19 and the studies by Cardozo et al, 22 Batista et al, 24 and Morais et al. 28 Such frequencies differed from those of the studies by Cabral et al, 20 Santos et al, 25 Freitas et al, 26 and Valenzuela et al, 27 in which the major etiology of chronic kidney disease (CKD) was chronic glomerulonephritis, which usually affects younger populations. The mean BMI values found were similar to the results of Valenzuela et al, 27 but the groups were distinct, and further studies are required for such comparison.…”
Section: Discussionsupporting
confidence: 82%
“…A enfermagem, diante da orientação sobre o autocuidado e prescrição de enfermagem, tem o papel de conscientizar o indivíduo quanto à manutenção do peso na preservação de sua saúde e bem-estar, ressaltando os riscos de excesso hídrico e de morte prematura por complicações cardiovasculares (10,12,15,(19)(20)(21)(22) . Nesse aconselhamento, deve-se esclarecer que alguns alimentos como café, chá, sopa, sorvete, água de coco, melancia, abacaxi, laranja, tomate, alface, dentre outros, são ricos em água e devem ser incluídos no volume total de líquidos ingeridos, pois a maioria, não é considerada como parte da ingesta hídrica, acarretando a aumento da volemia e consequentemente à HAS (15,23) . Quanto ao tratamento medicamentoso do indivíduo com DRC, este se baseia no uso de hipotensores (9,24) .…”
Section: Discussionunclassified
“…Dentre eles, está a elevação do nível de paratormônio (PTH), que aumentado leva à mobilização óssea de cálcio culminando em doenças ósseas descritas pelos nefrologistas como osteodistrofia renal, na qual gera limitações físicas levando a dificuldade em caminhar, fazer esforço físico, subir escadas, correr, entre outras (27)(28)(29) . Neste contexto, a literatura reporta ser necessário que os profissionais de saúde aconselhem os pacientes quanto a outros métodos de prevenção referente à HAS, refletindo diretamente no pico hipertensivo interdialítico, como à adesão dos medicamentos, ingesta hídrica moderada, redução da ingestão de sódio, sendo fundamental a participação da enfermagem nestas intervenções (8,12,(19)(20)(21)(22)(23)(24) . De forma consistente, destaca-se a importância de inserir a educação em saúde no ambiente hospitalar, valorizando a sua relevância em toda a organização de saúde, a fim de que os indivíduos possam optar por decisões saudáveis, capazes de contribuir com a sua qualidade de vida (7,29) .…”
Section: Discussionunclassified
“…Prevalence of asymptomatic UTI varies from 0.01 to 0.07% [3, 5 and 6]. Screening children for detection of asymptomatic bacteriuria is strongly recommended for prevention of pyelonephritis and renal scarring [7]. Due to the adverse complications of asymptomatic UTI such as renal scars as well as the high costs of treatment, screening tests for UTI in children are necessary in terms of cost containment and health promotion.…”
Section: Introductionmentioning
confidence: 99%